PRN Medicines Optimization and Nurse Education - Mojtaba Vaismoradi; Sue Jordan; Flores Vizcaya-Moreno; Ingrid Friedl; Manela Glarcher (MDPI AG, 2020)
Medicines management is a high-risk and error prone process in healthcare settings, where nurses play an important role to preserve patient safety. In order to create a safe healthcare environment, nurses should recognize challenges that they face in this process, understand factors leading to medication errors, identify errors and systematically address them to prevent their future occurrence. "Pro re nata" (PRN, as needed) medicine administration is a relatively neglected area of medicines management in nursing practice, yet has a high potential for medication errors. Currently, the international literature indicates a lack of knowledge of both the competencies required for PRN medicines management and the optimum educational strategies to prepare students for PRN medicines management. To address this deficiency in the literature, the authors have presented a discussion on nurses' roles in medication safety and the significance and purpose of PRN medications, and suggest a model for preparing nursing students in safe PRN medicines management. The discussion takes into account patient participation and nurse competencies required to safeguard PRN medication practice, providing a background for further research on how to improve the safety of PRN medicines management in clinical practice.